2017
DOI: 10.1016/j.ijvsm.2017.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective study on cattle and poultry diseases in Uganda

Abstract: Cattle and poultry enterprises are among the major contributors to food security and socioeconomic empowerment of households in Uganda. However, various diseases constrain their productivity. A two-year retrospective study between April 2012 and March 2014 was conducted using records for cattle and poultry diseases diagnosed at the Central Diagnostic Laboratory (CDL) to determine prevalent diseases in Uganda. The laboratory received 836 samples from poultry (36.3%) and cattle (63.7%). Of the 836 samples, 47.5%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 18 publications
7
25
0
Order By: Relevance
“…It was not surprising to find that ECF was the most common TBD in both regions. This is in agreement with previous reports, which found a prevalence of over 90% of Theileria parva in bovine samples submitted for clinical examination at Veterinary Central Diagnostic Laboratory at Makerere University [ 15 ]. Another study by Muhanguzi et al [ 16 ] also emphasized the veterinary importance of ECF in cattle.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…It was not surprising to find that ECF was the most common TBD in both regions. This is in agreement with previous reports, which found a prevalence of over 90% of Theileria parva in bovine samples submitted for clinical examination at Veterinary Central Diagnostic Laboratory at Makerere University [ 15 ]. Another study by Muhanguzi et al [ 16 ] also emphasized the veterinary importance of ECF in cattle.…”
Section: Discussionsupporting
confidence: 93%
“…In both regions, ECF and coinfections of TBDs and mastitis were reported as the most common diseases affecting lactating cattle. This is further supported by previous published reports, which have consistently identified ECF as the most common disease affecting cattle in Uganda and neighboring countries [ 8 , 15 , 21 ]. Farms located in HARA were found to be practicing self-diagnosis and self-treatment of animal diseases without consulting the qualified veterinarian, and this was not any different in farms located in LARA.…”
Section: Discussionsupporting
confidence: 89%
“…Not much information exists for African countries, but in Nigeria, 40% of broiler mortality was caused by APEC, which led to a loss of several millions of dollars [5]. In Uganda, information on economic significance of colibacillosis is not available but it is the most frequent bacterial infection among the chicken samples submitted to the Central Diagnostic Laboratory with a prevalence of 14% [6].…”
Section: Introductionmentioning
confidence: 99%
“…Avian colibacillosis refers to any localized or systemic infection caused by Avian Pathogenic Escherichia coli (APEC) belonging to several serogroups; and remains one of the most prevalent bacterial diseases affecting the poultry industry worldwide [1]. In Uganda, colibacillosis is the most frequent bacterial infection among the chicken samples submitted to the Central Diagnostic Laboratory with a prevalence of 14% [2]. Majalija et al (2010) reported 87%…”
Section: Introductionmentioning
confidence: 99%